(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article discusses the interpretation of the concept of reduplication, its classification principles, and one of its specific subtypes in English. The formation rules and content of shm-reduplication are analysed through concrete examples.